(untitled) (Research, Society and Development, 2020)
Yeasts play a fundamental role in nature, and due to their biochemical and physiological versatility, many of them can have their metabolic routes regulated and optimized for the biosynthesis of specific products. In view of this potentiality, new contributions that dedicate to the study of fermentative processes involving yeasts as protagonists, especially for the production of value-added products from lost vegetables and their residues, show importance. Among these products, particularly in this brief review, the production of pectinase and yeast probiotic potential in alternative culture media is mentioned as a way to make these processes more economically and environmentally viable.